2017
DOI: 10.1111/evj.12764
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two blood sampling techniques for the determination of coagulation parameters in the horse: Jugular venipuncture and indwelling intravenous catheter

Abstract: With the exception of AT and D-dimers, coagulation parameters measured on blood samples obtained via an IVC have clinically equivalent values to those obtained by jugular venipuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…There was concern about using only paired t-test and Wilcoxon signed rank test comparison methods; often, the differences may be statistically significant yet not clinically meaningful. Therefore, agreement between the two methods is tested using the Bland-Altman plots [11][12][13]16,17 along with a clinically accepted interval (CAI) estimated a priori and based on clinical expertise. Bland-Altman plots (►Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was concern about using only paired t-test and Wilcoxon signed rank test comparison methods; often, the differences may be statistically significant yet not clinically meaningful. Therefore, agreement between the two methods is tested using the Bland-Altman plots [11][12][13]16,17 along with a clinically accepted interval (CAI) estimated a priori and based on clinical expertise. Bland-Altman plots (►Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the Portacath study (5 mL vs. 2 mL, 3 mL, 4 mL, and 5 mL discarded volumes), the result indicates that there is lesser difference in the 3 mL and 5 mL discarded volumes. 1 While assessing the agreement between 3 mL and 5 mL discarded volume methods for the six parameters, the Bland-Altman agreement limits [11][12][13]16,17 for sodium, potassium, creatinine, and direct bilirubin were not found within the CAI (as defined a priori and based on clinical expertise). The percentage of samples resulting in such a deviation for sodium, potassium, and direct bilirubin are 6.25% (95% CI 2.46-15%) and for creatinine are 7.81% (95% CI 3.38-17%), which is considered small and clinically insignificant as the deviation is found in less than 10% of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective study by Catriona Mackenzie and colleagues in the UK aimed to compare coagulation parameters of blood collected by direct jugular venipuncture and through an indwelling intravenous catheter (IVC) .…”
Section: Blood Coagulation Parametersmentioning
confidence: 99%
“…In horses, May et al 7 demonstrated that haematological and biochemical values obtained from blood samples collected via IVC are comparable to those obtained from blood collected by direct venipuncture. Clinical equivalence of coagulation parameters has been reported between the two techniques in dogs and horses 3,5,8,10 …”
Section: Introductionmentioning
confidence: 98%
“…There are some existing veterinary studies on the effect of blood collection by IVC on blood parameters 3,5‐10 . In horses, May et al 7 demonstrated that haematological and biochemical values obtained from blood samples collected via IVC are comparable to those obtained from blood collected by direct venipuncture.…”
Section: Introductionmentioning
confidence: 99%